Trait-mediated effect of arbuscular mycorrhiza on the competitive effect and response of a monopolistic species - Gross, Nicolas (2010)
1. Cessation of agricultural practices often leads to a dramatic decline in species diversity concomitant with the increase in abundance of monopolistic species, which have been hypothesized to be strongly arbuscular mycorrhiza (AM) dependent. AM can affect competitive interactions and influence plant species diversity. Few studies have tested AM effects on the competitive strategy of monopolistic species although it has been shown to be a key parameter to explain their high dominance. In addition, it is not clear whether AM effects on plant interactions can be explained by density-mediated interactions or by trait-mediated interactions. 2. We measured the competitive effect of Festuca paniculata, a widespread monopolistic species from subalpine communities, on itself and on two additional target species with and without AM (benomyl treatment) under contrasted fertilised treatments. AM effects on target species traits were quantified. 3. The three target species exhibited contrasted AM dependency and only F. paniculata was positively affected by AM presence in fertilised conditions. In the fertilised treatment, AM decreased intra-specific competition and increased inter-specific competition. Changes in competitive responses were explained by the AM effect on P inflow and species lateral spread. 4. Our results highlight AM ability to modify the performance of monopolistic species under different environmental conditions. AM provide an important mechanism by which monopolistic species can maintain a high level of dominance and dramatically decrease species diversity following agricultural abandonment.